Ability-based emotional intelligence in schizophrenia. Issue 3 (May 2017) - Frajo-Apor, Beatrice; Hofer, Alex
Abstract : Purpose of review: As one part of social cognition, emotional intelligence is a controversially discussed construct. Although well founded critique on the conceptualization of emotional intelligence has emerged over the last years, studies about emotional intelligence – especially the ability-based approach by Mayer and Salovey – can persistently be found in schizophrenia research. Recent findings: Studies published between October 2015 and October 2016 were included in this review. The majority of the studies addressed the associations between ability-based emotional intelligence and other clinical or neuropsychological features, for example symptom severity or executive functioning. One study investigated the effect of oxytocin on emotional intelligence and another dealt with the question, whether emotional intelligence could be an endophenotype for schizophrenia. Summary: The reviewed literature reveals that patients with schizophrenia exhibit impairments in ability-based emotional intelligence. In this context, non-social cognition, positive symptoms, and anomalous-self experiences seem to be of major relevance. The potential endophenotypic role of ability-based emotional intelligence in schizophrenia remains to be clarified.